2023
DOI: 10.1186/s12879-023-08202-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of clinically isolated methicillin-resistant Staphylococcus aureus (MRSA) and its susceptibility to linezolid and vancomycin in Egypt: a systematic review with meta-analysis

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen that causes severe morbidity and mortality worldwide. For the establishment of national strategies to combat MRSA infection in each country, accurate and current statistics characterizing the epidemiology of MRSA are essential. The purpose of this study was to determine the prevalence of MRSA among Staphylococcus aureus clinical isolates in Egypt. In addition, we aimed to compare different diagnostic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…In the same vein, Helmy et al 24 reported that the MRSA culture results had low resistance rates against tigecycline and linezolid. Furthermore, a meta analysis included 64 studies concluded that resistance of MRSA slightly changed post COVID-19 pandemic, with reserved susceptibility to vancomycin, tigecycline, or linezolid 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, Helmy et al 24 reported that the MRSA culture results had low resistance rates against tigecycline and linezolid. Furthermore, a meta analysis included 64 studies concluded that resistance of MRSA slightly changed post COVID-19 pandemic, with reserved susceptibility to vancomycin, tigecycline, or linezolid 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of clinically isolated MRSA in Egypt is notably high at 63% (17). Variations in MRSA prevalence across different regions of Iran may be due to differences in infection control practices, healthcare conditions, antibiotic prescription practices, selective antibiotic pressure in hospitals, and underlying clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that the use of β-lactam, macrolide, and lincosamide antimicrobial agents should be reduced. Therefore, in the medical environment, we need to use antibiotics carefully, 39 strengthen the monitoring of drug resistance, and choose antibiotics rationally according to the results of drug sensitivity. The dosage of antibiotics should be strictly controlled, and the rotation of drugs and withdrawal period should be strictly implemented.…”
Section: Discussionmentioning
confidence: 99%